Pathways to deviance: exploring the relationship between peer affiliation, gang membership and youth misconduct - Phillips, Ashwill Ramon (UNISA Press, 2021)
Deviant peer affiliation and gang membership often act as a catalyst for maladaptive behaviour, as individuals in the late adolescent phase of lifespan development typically share stronger attachment to their peers than to their caregivers. An interrelationship also exists between delinquency and factors such as peer approval of deviance and peer pressure to transgress. This is particularly prevalent when exposed to challenges in the family or school, which typically perpetuate feelings of rejection, leading to a greater likelihood to seek out peers to gain a sense of belonging, support and camaraderie. Despite the importance of these interactions, exposure to antisocial peers or gangs exponentially increase the propensity to transgress, as maladaptive behaviour would be reinforced, thereby decreasing the efficacy of primary and secondary socialisation agents. Moreover, youths may become desensitised to violence, learn to rationalise unlawful behaviour and gain opportunities for crime. Accordingly, a qualitative study was conducted in South Africa to explore peer affiliation and gang membership as a pathway to deviance, based on the unique experiences of 20 detained male youths. The data were obtained through purposive sampling and analysed by frequency or percentage distributions, and also through narrative accounts from the participants. The findings identified deviant peer affiliation (75%) and gang involvement (65%) as key factors which motivated the participants to transgress. Furthermore, the association between peer affiliation, substance abuse, academic failure and truancy was apparent. It is thus envisaged that these findings will stimulate further research, contribute to the existing literature and aid in the development of strategies to manage deviant peer association and gang membership.
Keywords: Youth misconduct; Criminogenic risk factor; Peer affiliation; Gang membership